Low-Dose Actinomycin-D Induces Redistribution of Wild-Type and Mutated Nucleophosmin Followed by Cell Death in Leukemic Cells - Brodská, Barbora; Holoubek, Aleš; Otevřelová, Petra; Kuželová, Kateřina (Journal of cellular biochemistry, 2016)
Specific mutations involving C-terminal part of the nucleolar protein nucleophosmin (NPM) are associated with better outcome of acute myeloid leukemia (AML) therapy, possibly due to aberrant cytoplasmic NPM localization facilitating induction of anti-NPM immune response. Actinomycin D (actD) is known to induce nucleolar stress leading to redistribution of many nucleolar proteins, including NPM. We analyzed the distribution of both wild-type and mutated NPM (NPMmut) in human cell lines, before and after low-dose actD treatment, in living cells expressing exogenous fluorescently labeled proteins as well as using immunofluorescence staining of endogenous proteins in fixed cells. The wild-type NPM form is prevalently nucleolar in intact cells and relocalizes mainly to the nucleoplasm following actD addition. The mutated NPM form is found both in the nucleoli and in the cytoplasm of untreated cells. ActD treatment leads to a marked increase in NPMmut amount in the nucleoplasm while a mild decrease is observed in the cytoplasm. Cell death was induced by low-dose actD in all the studied leukemic cell lines with different p53 and NPM status. In cells expressing the tumor suppresor p53 (CML-T1, OCI-AML3), cell cycle arrest in G1/G0 phase was followed by p53-dependent apoptosis while in p53-null HL60 cells, transient G2/M-phase arrest was followed by cell necrosis. We conclude that although actD does not increase NPM concentration in the cytoplasm, it could improve the effect of standard chemotherapy in leukemias through more general mechanisms.
Keywords: mutace; HeLa Cells; Nuclear Proteins; apoptóza; vztah mezi dávkou a účinkem léčiva; HL-60 buňky; LEUKEMIA; daktinomycin; jaderné proteiny; Apoptosis; Cell Nucleolus; lidé; HeLa buňky; Cell Cycle Checkpoints; kontrolní body buněčného cyklu; nukleofosmin; Dactinomycin; Mutation; HL-60 Cells; APOPTOSIS; ACTINOMYCIN D; Dose-Response Relationship, Drug; Nucleophosmin; leukemie; MUTATED NUCLEOPHOSMIN; Leukemia; Cytoplasm; Cell Survival; viabilita buněk; P53-DEFICIENCY; buněčné jadérko; cytoplazma; Humans